Dendritic molecules give excellent long‐lasting desalination fouling resistance to reverse osmosis membrane by generating an amine‐rich layer. Issue 17 (30th December 2018) - Chen, Li‐Ye; Zhang, Pan; Gai, Jing‐Gang
ABSTRACT: The organic fouling of polyamide membranes is one of the most serious problems in reverse osmosis fields such as sea water desalination and sewage disposal. In this study, poly(ethylene imine)–poly(ethylene glycol) dendrimer is used to improve the fouling resistance of polyamide reverse osmosis membranes. A crucial pretreatment is carried out with a reaction between poly(ethylene imine) and acyl chloride on the nascent polyamide surface, generating an amine‐rich selective layer. Poly(ethylene glycol) diglycidyl ether is then attached to the primary amine group. The results illustrate a remarkable improvement in membrane surface hydrophilicity after modification (the contact angle decreases from 96.7° to 49.5°). Dynamic fouling tests are implemented with bovine serum albumin as a typical protein foulant, in which the membranes show very low protein adsorption (flux recovery ratio 96.9%). After 11‐cycle fouling tests, the membranes show excellent long‐term stability and remarkable antifouling property and cleaning performance. This approach of grafting a dendrimer might provide new insight for antifouling modifications for membranes. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47368. Abstract :